Highly efficient adsorption of radioiodine by a three-dimensional ordered macroporous bismuth-silica composite aerogel. (12th October 2022) - Chang, Sen; Wang, Kunjun; Gao, Linfeng; Liu, Jingguo; Wang, Longjiang; Li, Yongguo; Song, Xuemei; Yu, Jie; Luan, Xin'gang
Graphical abstract: Three-dimensional ordered macroporous structure and dispersed active ingredient nano bismuth provides silica aerogel with ultrahigh iodine capture capacity (up to 696±21 mg/g) by increasing physisorption and enhancing the chemical reaction between Bi and I2 . Highlights: A three-dimensional ordered macroporous bismuth-silica (3DOM-SB) was prepared. The detected iodine adsorption capacity of 3DOM-SB aerogel reaches 696 ± 21 mg/g. The iodine capture mechanism of 3DOM-SB aerogel was revealed. An effective strategy for achieving high iodine capture capacity is proposed. Abstract: At present, the iodine adsorbents used in the post-treatment iodine removal system are silver-loaded zeolites (AgZ and AgX), because silver and iodine have higher reactivity. The main advantages of bismuth over silver in iodine capture include high-cost performance, non-toxicity and high adsorption capacity. In this work, the sol–gel method combined with the colloidal crystal template method was used to introduce the three-dimensional ordered macroporous structure into the bismuth-silica aerogels. The detected adsorption capacity reaches 696 ± 21 mg/g, which is approximately 3-fold higher than that of silver-loaded zeolites. And the adsorption mechanism of iodine by the bismuth-silica aerogels was revealed. It is found that the bismuth-silica aerogels have chemical adsorption and physical adsorption for iodine, and BiI3 is mainly formed by the chemical reaction between Bi and I2 .